Tourism identity in social media: The case of Suzhu, a Chinese historic city (Transactions of the Association of European Schools of Planning, 2018)
In the context of tourism planning and promotion, there is wide acknowledgement that conceptualisations of tourism identity cannot be grounded merely in physical place, but should also encompass a wide range of factors including, for instance, cultural relations, tourist activities, and social networking. There are opportunities in late modern society for relating the identity of a city’s tourism with digitally-presented tourists’ perceptions and activities through social media studies. This research explores multiple research approaches to delineate the digital identity of Suzhou’s tourist destinations, as presented in online user-generated contents. It is hoped that this social media study can provide supplementary information for tourism bureaus and agencies to make informed judgements on effecting pertinent improvements to optimise existing tourism resources and create more enticing environments for tourists. The research follows a case study approach and conducts an empirical study on Suzhou, a Chinese historic city. The analysis of the results show that the social media study is potentially useful in identifying the key characteristics of particular tourist destinations from visitors’ perspectives that may also be helpful for the evaluation of tourists’ experiences.
Keywords: Tourism; social media; place identity